Assessment of Motor Performance and Self-Perceived Psychophysical Well-Being in Relation to Body Mass Index in Italian Adolescents - Gaetano Altavilla; Sara Aliberti; Francesca D'Elia (MDPI AG, 2024)
Background/Objectives: The relationship between psychophysical self-perception (PSP), body mass index (BMI) and motor performance (MP) levels, in quantitative and qualitative terms, can be a very interesting connection to investigate. This study aimed to assess MP and PSP according to gender and weight differences (normal weight-Nw/overweight-obese-Ov-Ob) and their relationship to BMI in Italian adolescents. Methods: In total, 144 students (F = 72; M = 72) aged between 11 and 13 y.o. participated in this study. They were divided into two groups by gender and into two subgroups based on weight (Nw/Ov-Ob). Standing long jump, sit-and-reach, 10 × 5 m shuttle and sit-up tests to assess MP were carried out, and an ad hoc questionnaire to evaluate PSP was administrated. Results: In comparing the Nw and Ov-Ob subgroups on the basis of BMI for each gender, statistically significant differences emerged in all motor skill tests administered. Regarding PSP, the Nw subgroup showed high and positive levels, while Ov-Ob showed low and negative levels, highlighting a relationship between high BMI and poor motor performance as well as negative psychophysical perception in the Ov-Ob subgroup. Conclusions: this study supports the importance of physical sport activity to regulate excess weight but also contribute to better psychophysical well-being.